Digestive enzymes during different life stages in three species of carps - Srikar, L N; Phadate, S V; Reddy, G Vidya Sagar (Indian Journal of Fisheries, 2011)
Kawai and Ikeda (1973) suggested that hatching enzymes consist of several hydrolases, including proteolytic and lipolytic enzymes. In carnivorous fish like salmon and black sea bream peptic activity, and in stomachless fish like common carp tryptic activity have a role in hatching (Kawai and Ikeda 1973).